2018
DOI: 10.3390/nu10091289
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Prevent Early Pancreatic Carcinogenesis via Repression of the AKT Pathway

Abstract: Pancreatic cancer remains a daunting foe despite a vast number of accumulating molecular analyses regarding the mutation and expression status of a variety of genes. Indeed, most pancreatic cancer cases uniformly present with a mutation in the KRAS allele leading to enhanced RAS activation. Yet our understanding of the many epigenetic/environmental factors contributing to disease incidence and progression is waning. Epidemiologic data suggest that diet may be a key factor in pancreatic cancer development and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…5 The body of literature surrounding effects of fatty acids on cancers is larger than that of CBD oil. Many in vitro studies have been conducted and provide evidence that fatty acids such as docosahexaenoic acid and eicosapentaenoic acid are effective in reducing cancer cell viability through a variety of mechanisms in human cell lines [19][20][21][22][23] ; however, only one in vitro study has been conducted in canine cell lines. 24 One in vivo study investigated supplementation of menhaden oil in dogs with nasal carcinoma and found it may alleviate inflammatory side effects of radiation therapy 25 while another found n-3 PUFA supplementation increased disease-free interval and survival time in dogs with lymphoma; however, arginine was also supplemented in this T A B L E 5 Time spent researching pet health topics, pet nutrition and nutritional supplements, proportion of pet owners feeding nutritional supplements and number of supplements fed per dog in dogs with cancer and healthy dogs from an online dog owner survey regarding diet and supplement use Note: N, number of respondents; %, proportion; IQR, inter-quartile range reported as the range from Q1 to Q3; min, minimum; max, maximum.…”
Section: Discussionmentioning
confidence: 99%
“…5 The body of literature surrounding effects of fatty acids on cancers is larger than that of CBD oil. Many in vitro studies have been conducted and provide evidence that fatty acids such as docosahexaenoic acid and eicosapentaenoic acid are effective in reducing cancer cell viability through a variety of mechanisms in human cell lines [19][20][21][22][23] ; however, only one in vitro study has been conducted in canine cell lines. 24 One in vivo study investigated supplementation of menhaden oil in dogs with nasal carcinoma and found it may alleviate inflammatory side effects of radiation therapy 25 while another found n-3 PUFA supplementation increased disease-free interval and survival time in dogs with lymphoma; however, arginine was also supplemented in this T A B L E 5 Time spent researching pet health topics, pet nutrition and nutritional supplements, proportion of pet owners feeding nutritional supplements and number of supplements fed per dog in dogs with cancer and healthy dogs from an online dog owner survey regarding diet and supplement use Note: N, number of respondents; %, proportion; IQR, inter-quartile range reported as the range from Q1 to Q3; min, minimum; max, maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids, mainly containing the ω3 and ω6 families, dually affect pancreatic cancer. ω3 fatty acids inhibit cancer cell proliferation via reducing AKT phosphorylation, but ω6 fatty acids increase AKT phosphorylation [85]. However, a transcriptomics and metabolomics study revealed that lipase and a panel of fatty acids are significantly decreased in pancreatic tumors, and two saturated fatty acids, palmitate, and stearate, showed an obvious ability to inhibit the proliferation of pancreatic cancer cells [86].…”
Section: Lipidsmentioning
confidence: 99%
“…The P.J.G. laboratory has previously described the impact of a high-fat diet (HFD) enriched in polyunsaturated fatty acids on the progression of pancreatic neoplasia (31)(32)(33)(34). Given the connection between obesity and PI3K, this study includes cohorts of mice on an HFD enriched with ω-6 fatty acids.…”
Section: Significancementioning
confidence: 99%
“…As the HFD appears to establish a tumor permissive phenotype and activate AKT signaling independent of p110γ, we next evaluated the effects of in vitro p110γ inhibition when combined with administration of the main component of the in vivo HFD: ω-6 polyunsaturated fatty acids, in this case, linoleic acid (LA). We again used Panc-1, MiaPaca-2, and AsPC-1 PDAC cell lines and administered 40 μM of LA, the working concentration as previously determined empirically in our laboratory (34). In response to LA, each cell line displayed increased expression of p110α, p110β, and p110γ both at the mRNA (Fig.…”
Section: Genetic Ablation Of P110γ Reduces Panin Formation and Disrupmentioning
confidence: 99%